PS-021 Potentially inappropriate medicines for the elderly in third level hospital discharges. (24th March 2015) - Sotoca, JM; Lopez, M; Tuset, M; Codina, C
Abstract : Background: Medicines for which the risk of adverse drug events (ADE) exceeds their expected clinical benefit when they are given to elderly persons, and which can be replaced by better-tolerated alternatives, are called potentially inappropriate medicines (PIMs). The prevalence of PIMs might be considered as a quality indicator of prescribing practice in the elderly. Purpose: To study the prevalence of three PIMs for elderly patients in third level hospital discharges. Material and methods: Data were obtained from the pharmacy claims database between 1st January 2013 and 31st December 2013. Patients over 64 years old who had had at least one of the following PIMs dispensed in the community pharmacy during 2013 were included: fluoxetine (selective serotonin reuptake inhibitor (SSRI)) because of the risk of hyponatremia and central nervous side effects (nausea, insomnia, dizziness, confusion), glibenclamide (sulfonylurea) because of its high risk of hypoglycaemia, metoclopramide (prokinetic) because of its extrapyramidal side effects. The proportion of users of these PIMs was calculated and broken down by gender and age. Results: The percentage of elderly patients who were dispensed one of the selected PIMs for the three drug classes is shown in Table 1 . Conclusion: The percentage of PIMs in elderly patients is still considerable at discharge, at least for the three drugs considered. Stronger efforts should be made in medicines reviews at hospital discharge in order to minimise PIMs. Reference: Fick DM, et al . Updating the beers criteria for potentially inappropriate medication use in older adults. Arch Intern Med 2003;163(22):2716–24 No conflict of interest.